Primary Fistulotomy with Drainage Alone in Perianal Abscess: A Randomized Controlled Trial - Ghosh, Shishir Kumar; Sultana, Salma; Mamun, Md Abdullah Al; Masum, Md Nazmul Hoque; Hasan, A Z Mohamudul; Masum, Mohammad; Nahar, Jesmen; Das, Tapas Kumar; Mondal, Md Fahimul Islam; Paul, Sajib; Hasan, Mehfujul (Journal of Surgical Sciences, 2022)
Background: Perianal abscess is a clinical condition frequently encountered in daily surgical practice and recurrences may occur despite treatment with adequate incision and drainage. Most perianal abscess originates from an infected anal gland. Obstruction of these glands leads to stasis, bacterial overgrowth, and ultimately abscesses that are located in the intersphincteric groove. Primary fistulotomy may be advantageous for perianal abscesses because unlike ischiorectal abscesses, fistulas are more commonly found and can be laid open with full preservation of the external anal sphincters. Primary fistulotomy at the time of drainage for perianal abscesses results in fewer persistent fistulas and no added risk of fecal incontinence. Little clinical study has been performed in this issue. The aim of this study was to evaluate the early outcome of Primary Fistulotomy in case of Perianal Abscess at a tertiary level hospital. Study design: Randomized controlled trial. Study setting and period: Department of Surgery, Dhaka Medical College Hospital from 29th September 2018 to 28th September 2019. Methods: Randomized controlled trial. Result: It was observed that majority, e.g., 29.0% patients belonged to age 18-30 years. The mean age was found 35.4±8.5 years in Group-A and 35.1±9.2 years in Group-B. Male and female ratio was 3.87:1. Large numbers of respondents came from urban area (70.0%). It was evident from this study that, total 17 patients developed Abscess recurrence or purulent discharge from the site with group A predominance (14.0% vs. 3.0% in group-A and group -B respectively). Fistula formation was found in 12 patients in group A and 2 patients in group B. In this study 79 cases in group A while 96 cases in group B had detected healthy wound with good healing. Findings suggested that postoperative outcome was better in group B patients, the difference was statistically significant (p<0.05) between groups. In this study, it was observed that mean duration of surgery was 24.7±4.31 minute in group-A and 25.9±4.78 minute in group B patients. Similarly mean duration of healing was 27.5±5.23 days in group-A and 28.2±5.65 days in group B patients. Although operation time and healing duration was prolonged in group-B, but the difference was statistically non-significant (p>0.05) between groups. Present study demonstrated that, frequency of recurrence and fistular formation was 21% versus 4% in group-A and group-B respectively. Therefore perianal abscess surgery through the combined maneuver of incision – drainage with fistulotomy is associated with better outcome. Conclusions: Although both procedures are simple and easy to perform, drainage & fistulotomy appears to produce the better postoperative outcome, healing rate, with the fewest complications. Journal of Surgical Sciences (2022) Vol. 26(1) : 25-34